Relationship Between Child Marriage with Reproductive Health and Cervical Neoplasia in Karnali, Nepal - Thapa, Niresh; Maharjan, Muna; Shrestha, Girishma; Maharjan, Narayani (Journal of Karnali Academy of Health Sciences, 2021)
Background: Child marriage (marital age less than 18 years) is recognized as a violation of human rights. However, it remains a deep-rooted social problem in Nepal. We aimed to find out the relationship between child marriage and reproductive health and cervical neoplasia.Methods: A cross-sectional study was conducted from March 2016 to January 2017 in the Jumla district of Karnali province, Nepal. Apparently healthy, married women ages 20–65 were invited to participate in a cervical screening awareness program followed by an interview and examination. Interviews to obtain sociodemographic and reproductive health information were followed by cervical cancer screening by cytology and visual tests.Results: Out of 2190 eligible participants, 1450 (66%) reported child marriage. Illiteracy, smoking, multiparity, number of living children, and abortion rates were all significantly higher among the women who had a marital age of less than 18. Reports of abnormal cytology, visual inspection with acetic acid, and Lugol's iodine were not significantly different among the two groups of women who married before or after the age of 18.Conclusions: Child marriage is highly prevalent in Jumla, Karnali of Nepal and is associated with poorreproductive health outcomes, but is not significantly associated with an increase in cervical neoplasia as judged by visual inspection or cytology. It is highly recommended that child marriage in Nepal be prevented by improving awareness of the risks of child marriage, education, socioeconomic status, and strict implementation of the existing marriage age law.